Oral Health Promotion Implications of the Knowledge, Attitudes, and Behavior of Parents and Caregivers of Preschoolers in Tobruk City and Its Suburban Areas. - ELallaky, Hend; Zinelabedin Mohamed; Donia Salem; Khawla Haroun; Monia Abdullah; Rahma Elhammali; Zainab Moftah (AlQalam Journal of Medical and Applied Sciences, 2025)
This paper aimed to describe the oral health knowledge, attitudes, and behavior of parents and caregivers of preschool children in Tobruk city and its suburbs to enhance oral health promotion. In this cross-sectional study, 299 participants were selected at random from among Libyan citizens to provide a community overview. The overview was adapted for both paper and Google Forms® based on previous inquiries regarding surveys. The results show that about 35 % of parents disagreed with starting to brush their children's teeth when the first tooth appears, whereas more than half were unsure about the proper timing for the first dental visit, suggesting a significant knowledge gap that may delay early intervention and preventive care. In conclusion, a considerable level of unawareness and negative attitudes of parents about their children's oral health status is concerning the need for enhanced public education and outreach efforts.